High levels of adherence to a rectal microbicide gel and to oral Pre-Exposure Prophylaxis (PrEP) achieved in MTN-017 among men who have sex with men (MSM) and transgender women - Alex Carballo-Diéguez (2018)
© 2017, Public Library of Science. All rights reserved. This is an open access article, free of all copyright, and may be freely reproduced, distributed, transmitted, modified, built upon, or otherwise used by anyone for any lawful purpose. The work is made available under the Creative Commons CC0 public domain dedication. Trials to assess microbicide safety require strict adherence to prescribed regimens. If adherence is suboptimal, safety cannot be adequately assessed. MTN-017 was a phase 2, randomized sequence, open-label, expanded safety and acceptability crossover study comparing 1) daily oral emtricitabine/tenofovir disoproxil fumarate (FTC/TDF), 2) daily use of reduced-glycerin 1% tenofovir (RG-TFV) gel applied rectally, and 3) RG-TFV gel applied before and after receptive anal intercourse (RAI)—if participants had no RAI in a week, they were asked to use two doses of gel within 24 hours. Product use was assessed by mixed methods including unused product return count, text messaging reports, and qualitative plasma TFV pharmacokinetic (PK) results. Convergence interviews engaged participants in determining the most accurate number of doses used based on product count and text messaging reports. Client-centered adherence counseling was also used. Participants (N = 187) were men who have sex with men and transgender women enrolled in the United States (42%), Thailand (29%), Peru (19%) and South Africa (10%). Mean age was 31.4 years (range 18–64 years). Based on convergence interviews, over an 8-week period, 94% of participants had ≥80% adherence to daily tablet, 41% having perfect adherence; 83% had ≥80% adherence to daily gel, 29% having perfect adherence; and 93% had ≥80% adherence to twice-weekly use during the RAI-associated gel regimen, 75% having perfect adherence and 77% having ≥80% adherence to gel use before and after RAI. Only 4.4% of all daily product PK results were undetectable and unexpected (TFV concentrations < 0.31 ng/mL) given self-reported product use near sampling date. The mixed methods adherence measurement indicated high adherence to product use in all three regimens. Adherence to RAI-associated rectal gel use was as high as adherence to daily oral PrEP. A rectal microbicide gel, if efficacious, could be an alternative for individuals uninterested in daily oral PrEP.